Closing Remarks: Notes on Weber and Characterology. Reading "Science as a Vocation" with Hunter and Tribe - Du Gay, Paul (Sociologica (Bologna), 2018)
In "Science as a Vocation", Weber encourages his audience to be "polytheistic", and to take on the persona specific to the life order within which they are engaged. In the absence of a universal moral norm, or a conclusive victory for one form of organized rationality over all others, Weber asks, how are individuals to develop "character"? Weber's concern is the cultivation of individuals willing and able to live up to the ethical demands placed upon them by their location within particular life-orders, whose life-conduct within those orders and powers – the university, the public bureau, the firm – can combine practical rationality with ethical seriousness. These notes consider Weber as a late, great exponent of the "ethics of office" and in so doing seeks to indicate the continuing importance of his ethical stance.